IMPACT OF SOLAR RADIATION MODIFICATION ON TEMPERATURE CHANGES FROM SINABUNG ERUPTION IN KARO REGENCY - Koesuma, Sorja; Sakhina, Friska Ayu; Gernowo, Rahmat (JOURNAL ONLINE OF PHYSICS, 2025)
This study combines reanalysis of observational data and climate modelling to examine temperature changes due to the eruption of Mount Sinabung and future temperature projections. Observation data were taken from ERA5 to identify local temperature changes following the Sinabung eruption in February 2018, while simulations from the Geoengineering Model Intercomparison Project (GeoMIP) were used to observe temperature responses under the Solar Radiation Modification (SRM) scenario. Temperature projections were conducted for the period 2026 – 2099 using the CESM-WACCM, CNRM-ESM2-1, and MPI-ESM1-2-LR models under the G6Solar, G6Sulfur, SSP2-4.5, and SSP5-8.5 scenarios. The results show that GeoMIP temperatures are lower than ERA5 after bias correction. SRM was found to effectively decrease temperature at the summit of Sinabung and Karo Regency, approaching low emission scenarios (SSP2-4.5), with increases of 1,90℃ and 1,05℃ under G6Solar, and 1,02℃ and 0,96℃ under G6Sulfur. Conversely, in the high emission scenarios (SSP5-8.5), temperatures increased to 2,13℃ and 2,1℃.